Assessing what police officers do "on the job": toward a "public values" approach. Issue 1 (12th February 2018) - Caputo, Tullio; McIntyre, Michael Louis; Wang, Lucy Meng Yi; Hodgkinson, Tarah K.
Abstract : Purpose: The purpose of this paper is to present the results of a test in a policing context of a performance assessment tool that is based on a "public values" approach. The Capability, Importance, and Value (CIV) Tool allows police organizations to examine the roles their members carry out to determine whether they are being capably done, are important, and deliver value to stakeholders. Design/methodology/approach: Five focus groups were conducted with front line officers from a large Canadian police service. The focus group process incorporated elements of Appreciative Inquiry and Structured Brainstorming. Findings: Valuable information can be collected from front line police officers with the CIV Tool. Police organizations could use this information to improve performance while ensuring that the roles undertaken by their members align with broader organizational goals and objectives including providing value to stakeholders. Research limitations/implications: This study was designed as a limited test of the CIV Tool. More extensive testing is required with a larger sample that includes police investigators and members of other specialty units. Practical implications: The CIV Tool can serve to augment existing police performance measurement strategies. It can help to identify which roles contribute to achieving organizational goals and which do not. Based on this information, ameliorative action can be taken. Social implications: A "public values" approach places emphasis on stakeholder needs and expectations. Addressing these directly can result in enhanced performance as well as greater police transparency, responsiveness, and accountability. Originality/value: Ongoing police performance assessment based on a "public values" approach is uncommon in policing. Its use has important implications for police organizations and their stakeholders.